So for this, we will be setting up a system of equations with the information we have:
[tex]x+y=13\ \textsf{"The sum of two numbers is 13."}\\2x-3y=1\ \textsf{"Two times the first number minus three times the second number is 1."}[/tex]
Now we have our system of equations set up. Next, I will be using the substitution method to solve this system. So firstly, subtract y on both sides of the first equation:
[tex]x=13-y\\2x-3y=1[/tex]
Now, substitute x for (13 - y) in the second equation and solve for y as such:
[tex]2(13-y)-3y=1\\26-2y-3y=1\\26-5y=1\\-5y=-25\\y=5[/tex]
Now that we have the value of y, substitute it into either equation to solve for x:
[tex]x+5=13\\x=8\\\\2x-3(5)=1\\2x-15=1\\2x=16\\x=8[/tex]
In short, the first number (x) is 8 and the second number (y) is 5.